Risk Factors Associated to Retained Placenta in Holstein Cows - Gonçalves, Rodrigo Schallenberger; Guagnini, Fabio de Souza; Storck, Daniel Jonas; Brose, Mariana de Mattos; Diaz Gonzales, Félix Hilário; Cabrebra Dalto, André Gustavo (Acta Scientiae Veterinariae, 2019)
Background: Retained placenta (RP) is characterized by a failure to remove the fetal membranes within the first 12-24 h after calving. This condition appears to be related to a decrease in neutrophil activity and to the suppression of the immune response in the prepartum period. The specific reasons for some cows to retain the placenta after parturition is still not fully understood, but numerous predisposing factors have been related, which may include mechanical, nutritional, infectious and handling factors. The aim of this study was to analyze the occurrence of retained placenta in dairy cows and to correlate the main predisposing factors related. Materials, Methods & Results: This study was conducted in nine dairy farms located in the Rio Grande do Sul state, Brazil, with an average of 45 lactating dairy cows producing 10,100 kg / dairy cow in a period of 305 days. The total diet for postpartum cows was estimated to meet or exceed the requirements of dairy cows according to previously established guidelines (NRC 2001). A total of 393 calving Holstein cows (126 primiparous and 267 multiparous) were analyzed, of which 203 were kept in a semi-confined production system (free-stall and pasture system) and 190 animals were kept in a free-stall production system. Statistically, the cows were the experimental unit, and the results were analyzed using the Pearson’s Chi-squared test or Fisher’s exact test for the comparisons of occurrence of peripartum disorders. In addition, linear and logistic regression models were constructed to determine the effect of the dependent variable on the other indicators, which may be continuous or categorical. Possible correlations of the occurrence of peripartum disorders related to production system (free-stall or semi-confined), calving order (primiparous or multiparous), season of the year (heat or cold), ECC at calving (1 to 5), calf sex, rectal temperature and dystocia were analyzed. Of the 393 deliveries followed up in this study, 72 presented retained placenta as a postpartum complication. Cows that delivered male calves had a 3.45 times higher chance of presenting dystocia birth (P = 0.0007) and had 1.85 times more chances of presenting placental retention (P = 0.066) when compared to cows with female calves. Cows with dystocia were more likely to present RP (P = 0.0433). Twin pregnancies increased 3.9 times chances of RP (P = 0.0193). Discussion: The incidence of RP in our study was 18.3%, which is close to the previously reported by another Brazilian study (22%) and similar to another study that also verified the risk factor indicators (19.9%). Dystocia, twin births and male births were predisposing factors for RP, similarly to previous studies. The frequency of dystocia was significantly affected by the production system employed, with the semi-confined system presenting more cases of dystocia, unlike other studies. The season of the year had no influence in the RP occurrence, unlike other studies that showed RP may have an increase in spring and summer months. A possible correlation between RP and body condition score at calving and with the production system employed was not observed. The limited options of effective treatments for RP emphasizes the importance of prevention. RP prevention includes the reduction of stressful factors, especially in the peripartum period, with a focus one nutrition and animal health.